2007
DOI: 10.1007/s10552-007-9074-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parent characteristics and disease outcome framing on HPV vaccine acceptability among rural, Southern women

Abstract: Rural women, especially those who are younger, may be more accepting of the HPV vaccine when it is framed as a cervical cancer vaccine. Messages to mothers about the HPV vaccine for their daughters might be made more effective by framing the vaccine in terms of cancer and sexually transmitted disease prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 14 publications
3
27
1
1
Order By: Relevance
“…Weak tests of validity were performed in 16% of the studies [5, 8, 23, 24, 26, 29, 30, 34, 3739], primarily using expert opinion or qualitative evaluation. Two studies used focus groups to improve the content validity of survey items [8, 15]; ten reported having had items reviewed by a panel of experts or tested among similar populations [5, 8, 23, 24, 29, 30, 34, 3739]. Of the studies conducted in the U.S., only one developed an instrument for Spanish-speaking populations [37].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Weak tests of validity were performed in 16% of the studies [5, 8, 23, 24, 26, 29, 30, 34, 3739], primarily using expert opinion or qualitative evaluation. Two studies used focus groups to improve the content validity of survey items [8, 15]; ten reported having had items reviewed by a panel of experts or tested among similar populations [5, 8, 23, 24, 29, 30, 34, 3739]. Of the studies conducted in the U.S., only one developed an instrument for Spanish-speaking populations [37].…”
Section: Resultsmentioning
confidence: 99%
“…Items were categorized as “vaccine acceptability” if they included the word “would,” as in “ Would you agree to vaccination …” or “ Would you accept the vaccine …” Of 31 (39%) studies that measured this construct, 21 measured parental acceptability of the vaccine for daughters [5, 7, 8, 12, 15, 25, 34, 38, 39, 44, 53, 58, 60, 61, 80–86]. Eighteen measured acceptability for oneself [7, 9, 10, 12, 25, 3436, 38, 48, 50, 61, 78, 80, 84, 85, 87, 88], and five inquired about the acceptability of vaccinating sons [60, 61, 74, 80, 84].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations